Seismic-Scale Evidence of Thrust-Perpendicular Normal Faulting in the Western Outer Carpathians, Poland - Jan Barmuta (MDPI AG, 2021)
Based on the interpretation of 2D seismic profiles integrated with surface geological investigations, a mechanism responsible for the formation of a large scale normal fault zone has been proposed. The fault, here referred to as the Rycerka Fault, has a predominantly normal dip-slip component with the detachment surface located at the base of Carpathian units. The fault developed due to the formation of an anticlinal stack within the Dukla Unit overlain by the Magura Units. Stacking of a relatively narrow duplex led to the growth of a dome-like culmination in the lower unit, i.e., the Dukla Unit, and, as a consequence of differential uplift of the unit above and outside the duplex, the upper unit (the Magura Unit) was subjected to stretching. This process invoked normal faulting along the lateral culmination wall and was facilitated by the regional, syn-thrusting arc–parallel extension. Horizontal movement along the fault plane is a result of tear faulting accommodating a varied rate of advancement of Carpathian units. The time of the fault formation is not well constrained; however, based on superposition criterion, the syn -thrusting origin is anticipated.